Circ_0000735 enhances the proliferation, metastasis and glycolysis of non-small cell lung cancer by regulating the miR-635/FAM83F axis. (16th March 2021) - Tai, Guigang; Zhang, Miao; Liu, Fang
Abstract: Background: Circular RNA (circRNA) is considered to be an important regulator of cancer malignant progression, including non-small cell lung cancer (NSCLC). Circ_0000735 has been found to be associated with NSCLC progression. Therefore, its role and molecular mechanism in NSCLC deserve further exploration. Methods: Quantitative real-time PCR (qRT-PCR) was used to measure the expression of circ_0000735, microRNA (miR)-635 and family with sequence similarity 83 member F (FAM83F). Cell proliferation, migration, invasion and apoptosis were determined using cell counting kit 8 assay, colony formation assay, transwell assay and flow cytometry. Cell glycolysis were measured by detecting the glucose consumption and lactate production of cells. Western blot analysis was utilized to test the protein levels of glycolysis markers and FAM83F. The relationship between circ_0000735 and miR-635 or miR-635 and FAM83F was verified by dual-luciferase reporter assay. The effect of circ_0000735 on NSCLC tumor growth was evaluated by constructing xenograft models. Results: Circ_0000735 was a highly expressed circRNA in NSCLC. Silenced circ_0000735 could inhibit NSCLC cell proliferation, migration, invasion, glycolysis, and increase apoptosis. MiR-635 could be sponged by circ_0000735, and its inhibitor could reverse the regulation of circ_0000735 silencing on NSCLC progression. Moreover, FAM83F was a target of miR-635, and circ_0000735 positively regulated FAM83F by sponging miR-635. The inhibitory effect of miR-635 on NSCLC progression could also be reversed by FAM83F overexpression. Additionally, circ_0000735 knockdown reduced NSCLC tumor growth through regulating miR-635/FAM83F axis. Conclusion: Circ_0000735 promoted NSCLC progression by the miR-635/FAM83F axis, showing that circ_0000735 might be a promising biomarker for NSCLC. Highlights: Circ_0000735 knockdown represses NSCLC cell progression and tumor growth. Circ_0000735 functions as a miR-635 sponge. FAM83F is targeted by miR-635.